The hidden dancers in water: the symbiotic mystery of Legionella pneumophila and free-living amoebae - Wang, Yuehua; Jiang, Linzhe; Zhou, Fei; Zhang, Yi; Fine, Ryan D.; Li, Mingguang (Frontiers in Microbiology, 2025)
Legionella pneumophila, a Gram-negative bacillus, is the primary etiological agent of Legionnaires’ disease, a severe respiratory infection. The symbiotic relationship between L. pneumophila and free-living amoebae (FLAs), particularly Acanthamoeba spp., represents a critical intersection of microbial ecology and human pathogenesis. This symbiosis provides Legionella with a protective intracellular niche, enhancing its resistance to biocides, increasing its pathogenicity, and facilitating horizontal gene transfer. These interactions not only boost the environmental persistence and dissemination of L. pneumophila but also elevate the risk of human exposure through contaminated drinking water systems. This review delves into the sophisticated survival strategies employed by L. pneumophila within host cells, including evasion of endocytic pathways, inhibition of phagosome maturation and acidification, and prevention of phagosome-lysosome fusion. By elucidating these mechanisms, we underscore the critical need for in-depth research into the Legionella-amoebae symbiosis and its broader implications for public health. Additionally, we address the challenges and strategies for mitigating environmental risks, emphasizing the importance of innovative approaches to ensure water system safety and prevent pathogen transmission.